Can extended reality in the metaverse revolutionise health communication? - Adéla Plechatá; Guido Makransky; Robert Böhm (npj Digital Medicine, 2022)
In the metaverse, users will actively engage with 3D content using extended reality (XR). Such XR platforms can stimulate a revolution in health communication, moving from information-based to experience-based content. We outline three major application domains and describe how the XR affordances (presence, agency and embodiment) can improve healthy behaviour by targeting the users’ threat and coping appraisal. We discuss how health communication via XR can help to address long-standing health challenges.